First record of Holcogaster fibulata in Slovenia (Heteroptera: Pentatomidae) - Gogala, Andrej (Acta entomologica slovenica (Ljubljana), 2023)
A specimen of Holcogaster fibulata (Germar, 1831) was found in Nova Gorica in August 2022. This is the first find of the species in Slovenia. The finding may show the spread of the species which is gaining ground also at the Atlantic coast of Europe.
Keywords: fauna; Hemiptera; prve najdbe; Slovenia; Slovenija; Stenice